TEKS KETTE KATONGA WERI KAWENDO PADA MASYARAKAT ADAT WEWEWA DI PULAU SUMBA: ANALISIS LINGUISTIK SISTEMIK FUNGSIONAL - Magdalena Ngongo (Kedeputian Bidang Ilmu Sosial dan Kemanusiaan (IPSK-LIPI), 2015)
Kette Katonga Weri Kawendo (KKWK) is one of marriage sessions called proposing to a girl practiced by Wewewa traditional society at Sumba island. This research is aimed to find out and describe text lexico-grammar, inter-clause relationship, context of situation, genre/structure, and ideology. The results show that text on lexicogrammar level covers transitivity, mood, and theme. (1) The transitivity indicated experiential meaning consists of three elements, (a) participant realized by noun and personal pronoun, (b) circumstance realized by adverbial and prepositional phrase, (c) process consists of six process types. (2).Mood realizing interpersonal meaning consists of indicative and imperative. It also has mood structure, such as affirmative is S^P); exclamation is EW^S^P; etc. Text appraisal concerns affect, judgment, and appreciation. (3) Theme realizing contextual meaning has three types: topical, interpersonal, and textual theme. Text thematic structure consists of interpersonal theme ^ textual ^ topical theme. Clause relation covers interdependency and logico-semantic. Context of situation covers field, tenor, and mode. The field relates to topics. Every stage has its own topic. Concerning to talking frequency, brides mediators status is higher than others. Based on topic discussed, tenors status is equal.Tenors have closed relationship. Text mode is spoken realized by the use of theme, Text genre is dialog of proposing to a girl. Generic structure covers various stages: preintroduction, introduction, content and closing. Each stage has sub-stages called. text generic potential structure. Text ideology is Watu nda ngeroka-Tana nda dikki Stone is not movedLand is not shifted. This ideology has six values.Keywords: KKWK, text, traditional society, Wewewa, Waijewa, SFL, Sumba